Human senses and sensors from Aristotle to the present - Brandt, Thomas; Dieterich, Marianne; Huppert, Doreen (Frontiers in Neurology, 2024)
This historical review on the semantic evolution of human senses and sensors revealed that Aristotle’s list of the five senses sight, hearing, touch, taste, and smell is still in use among non-scientific lay persons. It is no surprise that his classification in the work “De Anima” (On the Soul) from 350 BC confuses the sensor “touch” with the now more comprehensively defined somatosensory system and that senses are missing such as the later discovered vestibular system and the musculotendinous proprioception of the position of parts of the body in space. However, it is surprising that in the three most influential ancient cultures, Egypt, Greece, and China - which shaped the history of civilization - the concept prevailed that the heart rather than the brain processes perception, cognition, and emotions. This “cardiocentric view” can be traced back to the “Doctrine of Aristotle”, the “Book of the Dead” in ancient Egypt, and the traditional Chinese medicine of correspondence documented in the book “Huang di Neijing”. In Greek antiquity the philosophers Empedocles, Democritus and Aristotle were proponents of the allocation of the spirit and the soul to the heart connected to the body via the blood vessels. Opponents were the pre-Socratic mathematician Pythagoras, the philosopher Plato, and especially the Greek physician Hippocrates who regarded the brain as the most powerful organ in humans in his work “De Morbo Sacro”. The Greek physician Galen of Pergamon further elaborated on the concept of the brain (“cephalocentric hypothesis”) connected to the body by a network of nerves. The fundamental concepts for understanding functions and disorders of the vestibular system, the perception of self-motion, verticality and balance control were laid by a remarkable group of 19th century scientists including Purkynӗ, Mach, Breuer, Helmholtz, and Crum-Brown. It was also in the 19th century that Bell described a new sense of a reciprocal sensorimotor loop between the brain and the muscles which he called “muscular sense”, later termed “kinaesthesia” by Bastian and defined in 1906 as “proprioception” by Sherrington as “the perception of joint and body movements as well as position of the body or body segments, in space”.